2001
DOI: 10.1007/s002680020019
|View full text |Cite
|
Sign up to set email alerts
|

Transhiatal Esophagectomy for Treatment of Benign and Malignant Esophageal Disease

Abstract: Since our initial 1978 report, we have performed transhiatal esophagectomy (THE) in 1085 patients with intrathoracic esophageal disease: 285 (26%) benign lesions and 800 (74%) malignant lesions (4.5% upper, 22% middle, and 73.5% lower third/cardia). THE was possible in 97% of patients in whom it was attempted; reconstruction was performed at the same operation in all but six patients. The esophageal substitute was positioned in the original esophageal bed in 98%, stomach being used in 782 patients (96%) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
124
6
22

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(157 citation statements)
references
References 28 publications
5
124
6
22
Order By: Relevance
“…TTE with extensive lymph node dissection is applied as an extensive operation for the esophageal cancer which is mainly located within higher to middle thoracic esophagus. THE is mainly applied for the lower and abdominal esophagus 40 . Although the literature which compares TTE and THE with randomized study did not prove the statistically significant difference in long term survival of these two operations for thoracic esophageal cancer [41][42][43][44] , meta-analysis of these two procedures concluded that although TTE has a higher early morbidity in pulmonary dysfunction and mortality rate 13 , there was a trend regarding the improvement of the long term survival.…”
Section: Discussionmentioning
confidence: 99%
“…TTE with extensive lymph node dissection is applied as an extensive operation for the esophageal cancer which is mainly located within higher to middle thoracic esophagus. THE is mainly applied for the lower and abdominal esophagus 40 . Although the literature which compares TTE and THE with randomized study did not prove the statistically significant difference in long term survival of these two operations for thoracic esophageal cancer [41][42][43][44] , meta-analysis of these two procedures concluded that although TTE has a higher early morbidity in pulmonary dysfunction and mortality rate 13 , there was a trend regarding the improvement of the long term survival.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] A vantagem desta via de acesso é a de evitar o comprometimento da dinâmica pulmonar. Entretanto, pode haver a abertura da pleura e, como conseqüência, o desenvolvimento de hemo ou hidropneumotórax, acarretando maior morbidade pós-operatória.…”
Section: Introductionunclassified
“…The incidence of anastomotic leakage was higher than that of oesophageal reconstruction through the posterior mediastinum [9,10]. This incidence varied from 19 to 70% [11][12][13][14]. It has been reported that nearly 50% of cervical anastomotic leaks result from anastomotic strictures and the subsequent need for chronic dilatations, which negate the merits of an operation intended to restore comfortable swallowing [15].…”
Section: Discussionmentioning
confidence: 99%